Enhancement and optimization of exopolysaccharide production by Weissella confusa TISTR 1498 in pH controlled submerged fermentation under high salinity stress - Seesuriyachan,P. (Chiang Mai University, 2015)
There have been many reports that high concentrations of NaCl suppress the production of exopolysaccharide (EPS) in lactic acid bacteria (LAB). New evidence in this area has just revealed an enhancement of EPS production with a constant pH controlled (pH at 5.53) in submerged fermentation with a high concentration of NaCl (4%) and 100 g/l of sucrose. The high yield of EPS under the optimized condition was 63.8 g/l in the modified MRS medium. The EPS yield was 3.7 times higher than the yield (17.2 g/l of EPS) produced in an uncontrolled system. Moreover, the biosynthesis of EPS by Weissella confusa TISTR 1498 was independent of the biomass production. This evidence suggests that the controlled pH in submerged fermentation can compensate for the inhibitory effect under high salinity stress on EPS production.